2019
DOI: 10.1371/journal.pone.0214830
|View full text |Cite
|
Sign up to set email alerts
|

Genetic admixture patterns in Argentinian Patagonia

Abstract: As in other Latin American populations, Argentinians are the result of the admixture amongst different continental groups, mainly from America and Europe, and to a lesser extent from Sub-Saharan Africa. However, it is known that the admixture processes did not occur homogeneously throughout the country. Therefore, considering the importance for anthropological, medical and forensic researches, this study aimed to investigate the population genetic structure of the Argentinian Patagonia, through the analysis of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 27 publications
4
22
0
3
Order By: Relevance
“…The PCA shows that Argentinean individuals have different proportions of European, Native American and, much less represented, African ancestry (S1A Fig). This pattern, which has already been documented in other admixed populations from South America [31,42], including in Argentina [13][14][15][16]32] supports the heterogeneous genetic origins throughout the country. In addition, PC4 discriminates between Southern and Northern European individuals (S1B Fig) while PC6 separates Luhya population, a Bantu-speaking population in Kenya, from Western African populations (S1C Fig).…”
Section: Plos Onesupporting
confidence: 77%
See 2 more Smart Citations
“…The PCA shows that Argentinean individuals have different proportions of European, Native American and, much less represented, African ancestry (S1A Fig). This pattern, which has already been documented in other admixed populations from South America [31,42], including in Argentina [13][14][15][16]32] supports the heterogeneous genetic origins throughout the country. In addition, PC4 discriminates between Southern and Northern European individuals (S1B Fig) while PC6 separates Luhya population, a Bantu-speaking population in Kenya, from Western African populations (S1C Fig).…”
Section: Plos Onesupporting
confidence: 77%
“…The first systematic investigation of human genetic variation in Argentina focused on a limited number of markers either uniparental (mtDNA, Y-STRs, Y-SNP; [1][2][3][4][5][6][7][8][9][10] or autosomal (Short Tandem Repeats, Ancestry Informative Markers, Alu sequences, indels, and blood groups [11][12][13][14][15][16]). Studies based on autosomal markers identified an important inter-individual heterogeneity for the African, Native American and European genetic ancestry proportions [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using genetic markers with uniparental inheritance have shown an asymmetrical admixture of the ancestral European and Amerindian genomes by sex, as a consequence of Spanish men mating with Amerindian women during the first century of colonization, which has produced 84% Amerindian mitochondrial DNA [12] and less than 20% Amerindian Y chromosomes in the current Chilean population [13,14]. This asymmetrical admixture has also been demonstrated for other contemporary Latin American populations [15,16]. In recent years there have been two studies of continental ancestry using SNPs, one of them based on 30 ancestry-informative SNPs [17] and the other, genotyped with the Affymetrix GeneChip Array [18].…”
Section: Introductionmentioning
confidence: 96%
“…It has been proposed that panels of 100 SNPs provide reliable estimations of continental ancestry [21]. This technique has been used for some populations in southern South America; for instance, in Argentina using 99, 446 and 46 AIMs [16,22,23] and one study in Chile using a panel of 30 AIMs [17]. The aim of the present study was to design and test a panel of AIMs especially designed for the Chilean mestizo population, which is small enough to maintain genotyping costs low, but with enough number of SNPs to allow differentiating the Amerindian ancestries from the north (Aymara) and south (Mapuche) of the country.…”
Section: Introductionmentioning
confidence: 99%